Shotgun sequence-based metataxonomic and predictive functional profiles of Pe poke, a naturally fermented soybean food of Myanmar. - Jyoti Prakash Tamang; Pynhunlang Kharnaior; Priyambada Pariyar; Namrata Thapa; Ni Lar; Khin Si Win; Ae Mar; Nyo Nyo (PLoS ONE)
Pe poke is a naturally fermented sticky soybean food of Myanmar. The present study was aimed to profile the whole microbial community structure and their predictive gene functionality of pe poke samples prepared in different fermentation periods viz. 3 day (3ds), 4 days (4ds), 5 days (5ds) and sun-dried sample (Sds). The pH of samples was 7.6 to 8.7, microbial load was 2.1-3.9 x 108 cfu/g with dynamic viscosity of 4.0±1.0 to 8.0±1.0cP. Metataxonomic profile of pe poke samples showed different domains viz. bacteria (99.08%), viruses (0.65%), eukaryota (0.08%), archaea (0.03%) and unclassified sequences (0.16%). Firmicutes (63.78%) was the most abundant phylum followed by Proteobacteria (29.54%) and Bacteroidetes (5.44%). Bacillus thermoamylovorans was significantly abundant in 3ds and 4ds (p<0.05); Ignatzschineria larvae was significantly abundant in 5ds (p<0.05), whereas, Bacillus subtilis was significantly abundant in Sds (p <0.05). A total of 172 species of Bacillus was detected. In minor abundance, the existence of bacteriophages, archaea, and eukaryotes were also detected. Alpha diversity analysis showed the highest Simpson's diversity index in Sds comparable to other samples. Similarly, a non-parametric Shannon's diversity index was also highest in Sds. Good's coverage of 0.99 was observed in all samples. Beta diversity analysis using PCoA showed no significant clustering. Several species were shared between samples and many species were unique to each sample. In KEGG database, a total number of 33 super-pathways and 173 metabolic sub-pathways were annotated from the metagenomic Open Reading Frames. Predictive functional features of pe poke metagenome revealed the genes for the synthesis and metabolism of wide range of bioactive compounds including various essential amino acids, different vitamins, and enzymes. Spearman's correlation was inferred between the abundant species and functional features.